A study of the public schools division superintendency in the Philippines - Hipol, Purita B. (1974)
The socialization characteristics and value-commitments of 58 city and provincial public schools division superintendents including 8 randomly picked case respondents were studied to draw inferences regarding their administrative behavior and performance as agents of development. Individual value scores indicated the lowest commitment for Action Propensity and the highest commitment to Economic Equality. The respondents showed highest commitment to Economic Equality, Economic Development, and Selflessness and lowest commitment to Action Propensity, Conflict, Conflict Avoidance, and Local Concern. The socialization characteristics significantly related to value commitment are: sex, cultural grouping, place (urban/rural) of longest residence during childhood, region (Luzon, Visayas, Mindanao) of origin, income ratio, spouse's education and occupation, interpersonal communications, educational attainment, source of support for first college education and place (urban/rural) of longest service before entrance to superintendency.
Thesis (D.Ed.)--University of the PHilippines, Diliman.
Keywords: School superintendents and principals